PENGARUH PEMILIHAN INDEKS PASAR DALAM PEMBENTUKAN PORTOFOLIO MODEL INDEKS TUNGGAL - Ezra Putranda Setiawan (Department of Accounting, Faculty of Economics & Business, 2020)
Portfolio is a type of investment consists of several assets, such as stocks. Single index model is a portfolio optimization method that uses the market index value to calculate beta as a measure of asset’s performance. However, there are several market index available in Indonesia Stock Exchange. In this study, we examine and compare the performance of several market index to the portfolio’s performance that calculated using Single-Index Model. We choose several stocks that used in several market index, obtain the return data, and obtain the beta using several market index. The calculation of the optimal portfolio were repeated using 15 sets of data to obtain consistency. Based on the empirical study, we obtain that the way to choose the market index could affect the estimated beta as well as its standard error. However, it has a very small effect on the weight and the performance of the optimal portfolio.